TEACHING ENGLISH WITH INTERACTIVE TECHNIQUES AS A SECOND LANGUAGE TO YOUNG LEARNERS - Madina Togayeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In today’s world, knowing a second language has been not only a necessity but also a requirement for people in their professional success and career. This article is devoted to the analysis of teaching English with different methods to young learners.